2008
DOI: 10.1038/labinvest.2008.82
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 enhances adhesion, CD11b expression and survival in human eosinophils

Abstract: Eosinophils are important effector cells in allergic diseases, but the mechanisms regulating their biological functions remain obscure. Interleukin-33 (IL-33) is a recently identified cytokine of the IL-1 family, and it reportedly accelerates the production of Th2-associated cytokines and promotes tissue inflammation. However, the action of IL-33 on effector cells such as eosinophils has remained unclear. In this study, we investigated the effects of IL-33 on eosinophil activation, assessed in terms of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
155
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(164 citation statements)
references
References 32 publications
9
155
0
Order By: Relevance
“…IL-33 has been shown to prevent apoptosis in cardiomyocytes 60 and to promote the survival and viability of mast cells 61 as well as eosinophils. 62 More recently, IL-33 was shown to induce extracellular signal-regulated kinase (ERK) expression in lung epithelial cells. 63 UVB activation of ERK not only induces proliferation of human keratinocytes, 64 it promotes keratinocyte survival by down-regulating the tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10).…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 has been shown to prevent apoptosis in cardiomyocytes 60 and to promote the survival and viability of mast cells 61 as well as eosinophils. 62 More recently, IL-33 was shown to induce extracellular signal-regulated kinase (ERK) expression in lung epithelial cells. 63 UVB activation of ERK not only induces proliferation of human keratinocytes, 64 it promotes keratinocyte survival by down-regulating the tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10).…”
Section: Discussionmentioning
confidence: 99%
“…8,15,16 In addition, IL1b was identified as a potent mediator that initiates differentiation of Th17 lymphocytes to drive autoimmune responses, 17 while IL-18 was widely known as an inducer that stimulates IFN-c production from T lymphocytes and natural killer cells to promote Th1 responses. 18 Intriguingly, it has been reported that both IL-1b and IL-18 could also activate human eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 signals through a heterodimeric membrane receptor composed of ST2 and the IL-1R1 accessory protein and activates basophils [20,21], mast cells [22,23], eosinophils [24,25], NK and NKT cells [26], Th2 lymphocytes [5,27] and macrophages [14]. In accordance with its Th2 functions, administration of IL-33 into naive mice induces severe inflammation in the lung and digestive tract with elevated levels of IL-4, IL-5 and IL-13, splenomegaly and increased serum Ig [10].…”
Section: Introductionmentioning
confidence: 99%
“…J. Immunol. 2011 well documented [20,25]. Recently, it was shown that the resolution of allergic inflammation and airway hyperresponsiveness depend on the disruption of ST2/IL-33 pathway [8] and that IL-33-neutralizing antibody administration inhibits airway inflammation in mice [37].…”
mentioning
confidence: 99%